Targeted therapies mechanisms of resistance - Gioeli, Daniel (Molecular and Translational Medicine, 2011)
This volume explores the mechanisms of resistance to targeted therapeutics. The focus is on the cancer cell signaling network, although other mechanisms of resistance including target mutation, and new areas of study such as cancer stem cells are included.  Targeted Therapies: Mechanisms of Resistance highlights examples of changes in the signaling network in response to inhibition of a signaling event and underscores the importance in having a mechanistic understanding of the signaling network in cancer for developing effective targeted cancer therapies. Moreover, cutting edge tools to analyze the cell signaling network will be discussed. This includes the leading edge of techniques as well as computational biology and systems theory. This volume provides the reader with both an overview as well as a detailed perspective on the mechanisms of resistance to targeted therapeutics and will be of great value to the oncologist, the physician-scientist treating patients and the translational scientist working on any aspect of targeted therapeutics.